CHILDHOOD STUNTING IN RELATION TO ADOLESCENT LIVING ENVIRONMENT AND RESILIENCE: A FOLLOW UP STUDY IN LAHORE, PAKISTAN - Ekvall, Nils; Bengtsson, Linus; Kelly, Kristina Berg; Mellander, Lotta; Zaman, Shakila (Journal of Ayub Medical College Abbottabad, 2003)
Background: Stunting, as a manifestation of deprivation in early childhood, is a common problem among young Pakistani children. Poverty and lack of resources may predispose a child to maladjustment in the grown-up society. Resilience has been studied in young children to ascertain how the children cope with the challenges in life. The aim of the investigation was to study differences in growth, socio-economic situation and resilience between adolescent boys who had been stunted or normal in height at the age of five years. Methods: Using both quantitative and qualitative study designs, the study areas were an urban slum area and a village outside Lahore, Pakistan. All boys (n=36) had been followed from birth to 5 years of age in an earlier epidemiological study conducted at the Dept of Social and Preventive Paediatrics, King Edward Medical College, Lahore and were identified for follow up at 12-15 years of age. Results: Those who were stunted at 5 years were also shorter as adolescents than those who were normal in height at 5 years of age. Resilience, i.e., the combination of the adolescent's emotional abilities, his access to emotional and family support and view of himself was interestingly not heavily influenced by earlier malnutrition. Conclusions: Despite the hardships faced by the young adolescent boys, living in poor socio-economic situations, are capable of displaying resilience despite being stunted. Keywords: Adolescent boys, Stunting, Resilience, Pakistan.